Plastic Recycling Assessment Tool Based On Plastic Part Material And Disassembly Orientation - Fu Haw, Ho; Azrie Nazri, Mohamad Saiful (Research Progress in Mechanical and Manufacturing Engineering, 2021)
Improper plastic waste management and disposal is a global issue and yet still unsolved in many countries. The problem becomes worse when the recycler needs to deal with complex plastic products that could disable their initiatives to recycling. This study aims to conceptualize three main factors to influence plastic product recycling such as plastics grade, disassembly orientation, and different color into an assessment tool to evaluate the plastic product recycling performance. The data collection of this study was conducted based on Analytical Hierarchy Process (AHP) methodology before it was used for assessment tool development. The assessment tool has been reviewed and validated by two field experts in product design and green product field. The developed plastic recycling assessment tool could assist the industry practitioners especially the product designers in rethinking of their conceptual design that could ease the recycling activities.